Another world - Lyytinen, Erja; Assefa, Abdissa; Back, Tatu; Batten, Jennifer; Laitinen, Iiro; Landreth, Sonny; Taittonen, Harri (Tuohi Records, 2019)
8 kappaletta.
Keywords: Lyytinen, Erja, : 1976- : albumit